Mengidentifikasi Gagasan Pokok Paragraf Melalui Strategi Pembelajaran Partisipatif di Kelas IV SDN 1 Pangkalan Satu: Identifying the Main Ideas of the Paragraph Through Participatory Learning Strategies in Class IV SDN 1 Pangkalan Satu - Kasno, Kasno (Anterior Jurnal, 2022)
As happened in class IV Semester 1 of SDN 1 Pangkalan Satu that student achievement in Indonesian language lessons on identifying the main ideas of paragraphs is still low. The results of classroom action research (CAR) carried out by researchers showed that student learning achievement increased from before the action was implemented. From the first cycle to the second cycle, 26 students who finished studying or 100% of the total number of students had reached the KKM and even exceeded the class KKM target. Therefore, the Indonesian language learning material to identify the main idea of a paragraph with a participatory learning strategy for fourth-grade students is considered successful and the implementation stops in the second cycle.